A Clinical Guide to Epileptic Syndromes and their Treatment - Panayiotopoulos, C P.; SpringerLink (Online service) (London : Springer London, 2010)
This revised edition is indispensable reading for all those who care for patients with epileptic seizures. Building on the sell-out success of the first edition this thorough revision reflects the latest report of the ILAE classification core group and the significant progress made in the diagnosis, classification and treatment of the epilepsies. Praise for this edition "A Clinical Guide to Epileptic Syndromes and Their Treatment is well worth having in your library for its compendious information and significant update since its first edition (2002)... The text has truly become a pragmatic and helpful guide in the treatment of epilepsy." (George L. Morris III; JAMA) Praise for the first edition "This book is of great importance as the first one to cover epilepsy according to the new ILAE classification. It provides the necessary precondition for successful treatment management as well as for meaningful communication in the clinical and scientific community. " (Roger Weis; EJPN) "I recommend this book, the only one of its kind, to epileptologists, electrophysiologists, EEG technicians, neurologists, paediatricians, and even general physicians." (Nadir Bharucha; Lancet Neurology) "There are few books that a busy clinician will want to read from cover to cover whilst preparing a review $1 (Bthis is one of them." (Roger Cull; Brain) "Extremely well referenced$1! = (Ba useful source to the literature$1! = (Battractively presented, with colours used to highlight aspects such as definitions and some controversial issues$1! = (Bwell illustrated." (Sam Berkovic; Brain) "This book is a delightful rarity." (John Duncan; J Neurol Neurosurg Psychiatry) "I$1 (Bve read this book with interest, from end to end. It is fascinating, well- written and lively and makes the reader question his assumptions and procedures. Every person with an interest in epilepsy should read it." (Tim Betts; Seizure)s
General aspects of epilepsies -- Epileptic seizures and their classification -- Status epilepticus -- Imitators of epileptic seizures -- Epileptic syndromes and their classification -- EEG and brain imaging -- Principles of therapy in the epilepsies -- Neonatal epileptic seizures and neonatal epileptic syndromes -- Idiopathic epileptic seizures and syndromes in infancy -- Epileptic encephalopathies in infancy and early childhood -- Severe neocortical epileptic syndromes in infancy and childhood -- Benign childhood focal seizures and related epileptic syndromes -- Idiopathic generalised epilepsies -- Familial (autosomal dominant) focal epilepsies -- Symptomatic and cryptogenic (probably symptomatic) focal epilepsies -- Reflex seizures and related epileptic syndromes -- Diseases frequently associated with epileptic seizures -- Pharmacopoeia.
Keywords: Medicine; Neurology; Pediatrics; Medicine & Public Health; Neurology; Pediatrics